2014
DOI: 10.1007/s00595-014-1007-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the size of enlarged pelvic lymph nodes after chemoradiation therapy is associated with fewer lymph node metastases in locally advanced rectal carcinoma

Abstract: A reduction in the size of enlarged lymph nodes after neoadjuvant therapy may be a useful prognostic factor for recurrence and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The size of LNs is known to be important in treating cancer patients. Increased node size is associated with node metastasis and a poor prognosis (30), and reduction in the size of LNs reflects chemotherapeutic effects and fewer metastases (31). In our study, cervical cancer patients with small LNs showed a relatively low rate of lymphovascular space invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The size of LNs is known to be important in treating cancer patients. Increased node size is associated with node metastasis and a poor prognosis (30), and reduction in the size of LNs reflects chemotherapeutic effects and fewer metastases (31). In our study, cervical cancer patients with small LNs showed a relatively low rate of lymphovascular space invasion.…”
Section: Discussionmentioning
confidence: 99%
“…This study was restricted to colon cancer because of the commonly applied neoadjuvant therapy used in rectal cancer, which is well known to be an important factor that influences the number and size of retrieved lymph nodes [35]. Therefore, the inclusion of rectal cancers could have led to statistical bias.…”
Section: Discussionmentioning
confidence: 98%
“…8,14,20,21 Previous studies reported using the shrinkage percentage ((SA pre –SA restaging )/SA pre ×100%) of LLNs to reflect the responsiveness and predict the incidence of LPR. 20,22 By setting 60% as a cutoff value, the shrinkage percentage had shown the capacity to recognize patients at a higher risk of LPR. 22 In our study, we found nCRT group had a higher shrinkage rate than nCT group did.…”
Section: Discussionmentioning
confidence: 99%
“…20,22 By setting 60% as a cutoff value, the shrinkage percentage had shown the capacity to recognize patients at a higher risk of LPR. 22 In our study, we found nCRT group had a higher shrinkage rate than nCT group did. However, in univariable and multivariable analysis, we found no significant result in its prediction for LPR, even in the subgroup with positive pretreatment LLNs ( p = 0.15; HR, 0.227; 95% CI, 0.030–1.732).…”
Section: Discussionmentioning
confidence: 99%